Reformas laborales cubanas en la prensa mexicana. Análisis crítico del discurso de La Jornada y Reforma - Parrilla, Belén (2020)
The events in Argentina during the winter of 2018 (massive feminist groups marched to demand the approval of the Voluntary Termination of Pregnancy bill) invited us, from our places as artists, to emerge from our workspaces. The stage was set in the streets and the concept of art-life was about to manifest itself. Motivated to generate a device that expresses the politics of those who had abandoned their place of contemplation, questioned as individuals and mobilized as a collective, we decided to do an intervention with a performative aesthetic. This essay presents that feedback process between social and artistic performance, a reflection of the expressive and ungovernable limits of the green wave, and answers the call for a deep need to meet each other, taking over the public space, in a symbolic ex-pression of those of us who became protagonists in the construction of our rights. Every woman, all of us.